Toxicity profile of jamu sari rapet albumin and creatinine levels in female rats (Rattus norvegicus) - Ulfa, Darlah Immaria; Nuryady, Moh. Mirza; Wahyuni, Sri; Susetyarini, Rr Eko; Purwanti, Elly; Ariesaka, Kiky Martha; Fatmawati, Diani (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2023)
Married Madurese women routinely consume jamu sari rapet to please their husbands. There is no information on the toxicity test of jamu sari rapet.  The kidney is one of the organs that is targeted by toxic substances that enter the body. One of the parameters controlled is albumin and creatinine. The purpose of this study was to determine the effect on albumin and creatinine levels in white rats (Rattus norvegicus) given jamu sari rapet. This type of research is true experimental with a quantitative approach. This study was conducted for 28 days (subchronic). Data were analyzed using the Kruskal Wallis test. There were 4 groups, namely dose group 1 (1,56 g/gBB), dose group 2 (1,60 g/gBB), dose group 3 (1,66 g/gBB) and the control group. The results of this study showed no significant difference between albumin and creatinine levels compared to the control group. The conclusion shows that jamu sari rapet given to female rats (Rattus norvegicus) for 28 days has no significant effect on albumin and creatinine levels.